2004
DOI: 10.1109/tcsi.2004.826193
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Waveform Relaxation Methods for RC Type Circuits

Abstract: Waveform Relaxation has been widely used in circuit theory, for the solution of large systems of ordinary differential equations and the solution of partial differential equations. In the past, clever partitioning schemes have been used for circuit theory applications to enhance convergence. However, a drawback of the classical waveform relaxation algorithm is the non-uniform convergence over the window in time for which the equations are integrated. We propose a new optimized waveform relaxation algorithm whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
47
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
3

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 17 publications
0
47
0
Order By: Relevance
“…This can however be overcome with the newly developed class of optimized WR or oWR, see [9,[13][14][15]8,16], which has its roots in optimized Schwarz waveform relaxation methods, see [12,10,11,3] and also the related approach for circuits in [7,6]. In oWR, combinations of voltage and current values are transmitted at the interfaces between sub-circuits, and one can optimize the combination in order to obtain rapidly converging algorithms, which also led to the name oWR.…”
Section: Introductionmentioning
confidence: 99%
“…This can however be overcome with the newly developed class of optimized WR or oWR, see [9,[13][14][15]8,16], which has its roots in optimized Schwarz waveform relaxation methods, see [12,10,11,3] and also the related approach for circuits in [7,6]. In oWR, combinations of voltage and current values are transmitted at the interfaces between sub-circuits, and one can optimize the combination in order to obtain rapidly converging algorithms, which also led to the name oWR.…”
Section: Introductionmentioning
confidence: 99%
“…This was an essential step for the convergence of the WR algorithm for strongly coupled circuits such as directly coupled TL circuits. They demonstrated that this new technique can be applied effectively to diffusive circuits in [15] and to TL circuits in [16], without overlapping subcircuits. These new techniques are called optimized waveform relaxation (oWR) algorithms since they are based on an optimization process.…”
Section: Introductionmentioning
confidence: 99%
“…This is also an essential step in all of our strongly coupled circuit domain work. The first approach with the optimized transmission conditions in the circuit domain was presented for diffusive (RC) circuits in [26]. It was shown that new improved coupling between subsystems can greatly enhance the performance of WR methods.…”
Section: Introductionmentioning
confidence: 99%